Effects of Muscle Energy Technique vs Bruegger’s Relief Exercise on Forward Head Posture among electronic gadget users - Anam Dalawar, Hamna Afzal, Iram Dalawar, Ahmad Murtaza, Abdul Ghafoor, Shams Fiaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Neck pain due to Forward Head Posture (FHP) caused by prolongs flexion of head and neck while using electronic gadgets. It causes different musculoskeletal complaints particularly affecting upper limb and neck region. Muscle Energy Technique is an efficient method to reduce the tightness and improve strength of muscles. Bruegger’s Relief Exercise is helpful in improving posture. Aim: To compare the effects of Muscle Energy Technique (MET) and Bruegger’s Relief Exercise on pain, range of motion and function in patients of cervicalgia due to FHP. Method: A pilot study was performed. 24 subjects were recruited according to sample selection criteria and were assigned to Group A and B. Assessment of pain, function, Cervical ROM and Craniovertebral angle was taken using NPRS, NDI, Goniometer and photogrammetry. Group A received treatment with hot pack and Muscle Energy Technique. Group B received hot pack and Bruegger’s Relief Exercise. Total 20 sessions were given to each patient in 4 weeks with 5 sessions per week. Both groups were reassessed after 4 weeks of treatment. Data was analyzed by using SPSS 23. Results: There was statistically significant changes within both groups in the NPRS, NDI, CROM and Craniovertebral angle with p- value of < 0.05 Both were effective but using Bruegger’s Relief Exercise showed more improvement. Conclusion: Both treatment strategies were effective in decreasing pain, improving movement, regaining functional status, and correcting posture but using Bruegger’s Relief Exercise is more efficient for treating neck pain due to FHP.